Enhanced biodegradation of m-dichlorobenzene by Brevibacillus agri under the coexistence system of Zn(II) and Se(IV). Issue 1 (1st January 2020) - Yang, Bairen; Li, Yue; Shang, Qingqing; Wu, Menglei; Zhou, Qi; Xu, Qi; Ding, Cheng
ABSTRACT: Appropriate concentration of biological growth additives can improve the treatment effect of organic waste gas by microorganisms. In this work, the growth capability of Brevibacillus agri and the biodegradation efficiency of m-dichlorobenzene were investigated at the presence of Zn(II) and Se(IV). The appropriate concentration of Zn(II) and Se(IV) was 5 mg/L and 3 mg/L, and the removal efficiency of m-dichlorobenzene in the BTF achieved 94.95%. The functional groups such as C=O and COO- produced active sites to capture m-dichlorobenzene molecule, hence there existing a positive interaction process between the strain and Zn(II) and Se(IV). In the coexistence system, the polysaccharide and protein contents of EPS increased to 8.00±2.96 mg/L and 21.82±0.50 mg/L, the zeta potential value decreased 11.02 eV, the enzyme activity raised 3.2 mM, which indicated that the bioaugmentation effect on m-dichlorobenzene degradation could be achieved by the presence of Zn(II) and Se(IV).